Molecular determinants of prostate cancer metastasis - Rycaj, Kiera (Oncotarget, 2017)
Metastatic cancer remains largely incurable and fatal. The general course of cancer, from the initiation of primary tumor formation and progression to metastasis, is a multistep process wherein tumor cells at each step must display specific phenotypic features. Distinctive capabilities required for primary tumor initiation and growth form the foundation, and sometimes may remain critical, for subsequent metastases. These phenotypic features must remain easily malleable during the acquisition of additional capabilities unique and essential to the metastatic process such as dissemination to distant tissues wherein tumor cells interact with foreign microenvironments. Thus, the metastatic phenotype is a culmination of multiple genetic and epigenetic alterations and subsequent selection for favorable traits under the pressure of ever-changing tumor microenvironments. Although our understanding of the molecular programs that drive cancer metastasis are incomplete, increasing evidence suggests that successful metastatic colonization relies on the dissemination of cancer stem cells (CSCs) with tumor-regenerating capacity and adaptive programs for survival in distant organs. In the past 2-3 years, a myriad of novel molecular regulators and determinants of prostate cancer metastasis have been reported, and in this Perspective, we comprehensively review this body of literature and summarize recent findings regarding cell autonomous molecular mechanisms critical for prostate cancer metastasis.